Modification and optimization of boron carbide and zirconia as reinforcement in hot equal channel angular processing solid state recycling AA6061 aluminium - Mohammed Al-Alimi, Sami Abdo (2021)
The production of light metals reinforced with ceramic particles via Solid-State Recycling (SSR) is a cost-savings and have significant impacts on energy and green house. In this study, recycled aluminium 6061 (AA6061) chips reinforced with a different volumetric fraction of Boron Carbide (B4C), and Zirconia (ZrO2) by employing Response Surface Methodology (RSM) under 450°C, 500°C, 550°C preheating temperature to be processed by hot Equal Channel Angular Processing (ECAP). Considering the ECAP routes A the billet is to be pressed without rotation, route BA, the billet rotates 90° clockwise or counter clockwise, route BC the billet rotates 90° clockwise between the channels and route C the billet will rotate at an angle of 180°. Thus, the findings will be compared to the as-received materials. To reveal this, series of mechanical and physical tests on the aluminium chip-based composite to be developed needs to be carried out thoroughly. The compressive strength and hardness were 59.2 MPa and 69 HV that achieved at 5% of B4C and, 158 MPa and 74.95 HV achieved at routes A, B, C and D. Thus, it concluded that the B4C and number of passes have a significant effect on recycled AA6061 chips. But, for recycled AA6061/ZrO2 samples were obtained at 9.28% volume fraction and 550°C preheating temperature with values of (119.26MPa) compressive strength and 65.55 HV for microhardness. The distribution of particles with different mixed particles volume fractions were investigated by employing Scanning electron microscope (SEM) and Atomic Force Microscopes (AFM) tests. Furthermore, deformed-3D investigated the effects of die factors which have played an essential role in the magnitude of materials effective strain. Decreasing die angles leads to imposing more strain with higher punch force to the workpiece, which results in more homogeneity of the processed materials. Thus, the SSR via hot ECAP recycling process can produce a net shape structure utilises materials bonding consolidation at the time of providing sufficient supports to the reusing the recovered materials in the engineering applications such as automotive industries.